Kembara di bumi kenyalang - A. Samad Said (Abdul Samad Said), 1935- (Kuching, Sarawak : Tamar Media, 1998)
Essays on life in Sarawak in the 1990s.
In Malay.
Keywords: A. Samad Said -- 1935- -- Travel -- Malaysia -- Sarawak; Sarawak (Malaysia) -- Description and travel; Sarawak (Malaysia) -- Social life and customs